2014
DOI: 10.1002/hbm.22583
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane induces dose-dependent alterations in the cortical connectivity profiles and dynamic properties of the brain's functional architecture

Abstract: Despite their widespread use, the effect of anesthetic agents on the brain's functional architecture remains poorly understood. This is particularly true of alterations that occur beyond the point of induced unconsciousness. Here, we examined the distributed intrinsic connectivity of macaques across six isoflurane levels using resting-state functional MRI (fMRI) following the loss of consciousness. The results from multiple analysis strategies showed stable functional connectivity (FC) patterns between 1.00% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
130
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 113 publications
14
130
2
Order By: Relevance
“…The effects of isoflurane, the most commonly used anesthetic in monkeys, could be reflected as changes in the correlation strength between brain areas, localization, or inclusion of distributed nodes within specific networks (19,28). However, recent research has shown that within a carefully controlled narrow range of isoflurane levels, such as 6 .26% in our study, statistical coupling between brain areas was consistent and reliable for investigation of functional brain architecture (19,26). Moreover, we argue the potential effect of anesthetic agents was removed by contrasting the saline and ketamine treatments in the same group subjects and the thresholds for network construction were applied uniformly to each subject in both conditions.…”
Section: Regional Regulation Of Small-world Networkmentioning
confidence: 51%
See 1 more Smart Citation
“…The effects of isoflurane, the most commonly used anesthetic in monkeys, could be reflected as changes in the correlation strength between brain areas, localization, or inclusion of distributed nodes within specific networks (19,28). However, recent research has shown that within a carefully controlled narrow range of isoflurane levels, such as 6 .26% in our study, statistical coupling between brain areas was consistent and reliable for investigation of functional brain architecture (19,26). Moreover, we argue the potential effect of anesthetic agents was removed by contrasting the saline and ketamine treatments in the same group subjects and the thresholds for network construction were applied uniformly to each subject in both conditions.…”
Section: Regional Regulation Of Small-world Networkmentioning
confidence: 51%
“…Growing evidence has validated the use of restingstate functional magnetic resonance imaging (rsfMRI) in anesthetized macaques (19)(20)(21)(22)(23)(24)(25)(26)(27) and has underscored its potential to bridge information between human and animal models (28)(29)(30)(31). Although the effect of anesthetic agents on functional brain networks remains poorly understood, recent study has demonstrated that stable functional connectivity patterns under a narrow range of medium level isoflurane (e.g., 6.25%) are suitable for anesthetized nonhuman primate investigations (26). Furthermore, whole-brain rsfMRI allows unbiased, simultaneous identification of all pharmacologically affected regions in the brain.…”
mentioning
confidence: 99%
“…The macaque fMRI data were acquired under low-dose anesthesia, and although this method is known to produce robust patterns of FC that are homologous to human FC networks (57), it may affect the temporal structure of FC at higher doses (58). Interhemispheric FC, in particular, is vulnerable to isoflurane in a dose-dependent fashion (59), and this vulnerability may explain why the difference in FC strength between intrahemispheric and heterotopic connections was more pronounced in the macaque than in the human dataset. Future studies using fMRI acquired in awake animals will be needed to investigate cross-species differences in interhemispheric coordination more directly.…”
Section: Discussionmentioning
confidence: 99%
“…First, data were obtained under anesthesia to both maintain stable physiological conditions and to limit head movement. The resting-state fMRI signal in rats, as in other species (50,51), appears to be anesthetic dependent (52,53). However, Grandjean et al (51) suggested that the combined use of medetomidine and isoflurane maintains strong correlations within both cortical and subcortical structures in mice.…”
Section: Modulation Of Dmn Connectivity As a Function Of Age-relatedmentioning
confidence: 99%